Colony housing promotes structural and functional changes during surgically induced osteoarthritis in rats. Issue 4 (December 2020) - Brenneis, C.; Menges, S.; Westhof, A.; Lindemann, S.; Thudium, C.S.; Kleinschmidt-Doerr, K.
Summary: Objective: The aim of the study was to investigate how social housing with high locomotion activity affects experimental osteoarthritis (OA) in rats. Design: Rats were housed either conventionally in type IV cages in pairs or in rat colony cages (RCC) on 4 levels interconnected by jump holes or staircase in groups of 48. OA was induced by anterior cruciate ligament transection and resection of the medial meniscus (ACLT + tMx), medial meniscal tear (MMT) or destabilization of the medial meniscus (DMM). Functional changes were characterized by continues tracking of individual activity and catwalk gait analysis. Cartilage volume and bone structure were investigated at week 20 after surgery by histology and micro-CT. Results: In the RCC, healthy rats changed cage levels 82 ± 15 times daily, reduced by 30% after ACLT + tMx (p < 0.0001). In both housing systems, the order of severity of the investigated models was ACLT + tMx > MMT > DMM in all outcome measures. Compared to Type IV, RCC housed rats developed stronger gait disturbance symptoms (ACLT + tMx; 95%CI = −15-2; p < 0.004), the cartilage volume was reduced (ACLT + tMx: 95%CI = −0.1-0.5; p < 0.0001), serum levels of the cartilage remodeling marker AGNx1 were higher (MMT; 95%CI = −53-(-6); p = 0.001), bone was denser with increased volume (ACLT + tMx; 95%CI = 0.8–7.5; p = 0.004) and joints were less flexible (ACLT + tMx; 95%CI = 3.6–14; p < 0.0001). Conclusion: Housing rats in an environment allowing increased locomotion and socialization promotes structural and functional alterations during joint instability-induced OA. This increases the assay window, improves the relevance for the human disease and enables to discriminate the models in structural and behavioral parameters.